Epidemiology Of Viral Infections In Neonatal Intensive Care Unit. Maternal Perinatal National Institute 2013 - 2014 - Mendoza-Ibañez, Elina (2016)
Objective. To determine the epidemiology of viral infections in the NICU-INMP. Materials and Methods. Review of medical records of 50 patients with confirmed viral infection, in 2013-2014 in the NICU -INMP and descriptive statistical analysis using SPSS 23.